PENGARUH CURRENT RATIO, DEBT TO EQUITY DAN RETURN ON EQUITY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dwi Susilowati; Juwari Juwari; Dhita Septianti Khairunisa (Jurnal GeoEkonomi, 2023)
The purpose of this study was to determine the effect of Current Ratio, Debt to Equity Ratio and Return On Equity on Company Value (Price to Book Value) listed on the Indonesia Stock Exchange. In this study, the total population of 14 companies and a sample of 8 companies were taken using the criteria determined by the author. The data analysis method used is multiple linear regression analysis. The results of this study indicate that partially the Current Ratio variable has a positive and significant relationship to Firm Value (PBV) while the Debt to Equity Ratio has a positive and insignificant relationship to Firm Value (PBV) and Return On Equity has a positive relationship. positive and not significant to Firm Value (PBV)